Impossible things - Stevenson, Robin H. (Robin Hjordis), 1968- (Orca Book Publishers, 2008)
Cassidy Silver is accustomed to being the biggest freak in the seventh grade, but things start to change when Victoria, a new girl at school, chooses to be her friend, and the confidence she gains from having a friend spills over into other areas of Cassidy's life.